2006
DOI: 10.1002/elan.200603621
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Biofuel Cell Performance Using a Targeted Mixed Mediator Combination

Abstract: A study of how mediators might interact with the catabolic pathways of yeast was undertaken with a view towards improving the performance of microbial fuel cells. This work suggests that no single mediator is ideally suited to the task, and that a carefully selected mixture of two targeted mediators (Methylene Blue and Neutral Red) might be optimal. To test this hypothesis a yeast-catalyzed microbial fuel cell was built and empirically evaluated under different mediation conditions. The results clearly show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 10 publications
(8 reference statements)
0
17
1
1
Order By: Relevance
“…This increase in the performance was related to the role of the MB in the enhancement of the anaerobic respiration, while NR involved with fermentation only. This study [44] showed that the addition of the MB was effective than NR, which is in contradiction to that reported by Najafpour et al [49]. This might be related to the difference in the operation conditions, and/or any other reasons that is not clear for the authors right now.…”
Section: Mediated Yeast-based Mfccontrasting
confidence: 97%
See 3 more Smart Citations
“…This increase in the performance was related to the role of the MB in the enhancement of the anaerobic respiration, while NR involved with fermentation only. This study [44] showed that the addition of the MB was effective than NR, which is in contradiction to that reported by Najafpour et al [49]. This might be related to the difference in the operation conditions, and/or any other reasons that is not clear for the authors right now.…”
Section: Mediated Yeast-based Mfccontrasting
confidence: 97%
“…These mediators whether internal or external will be responsible for the electron transfer from the bulk microorganisms to the anode surface. The electron transfer in the mediated electron transfer is higher than that in the DET [4,[44][45][46][47][48][49][50][51].…”
Section: Indirect Electron Transfer Through External or Internal Medimentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6A shows that the phenothiazine-type mediators are better than phenazinetype mediators as also reported by Ieropoulos et al who tested different types of mediators for a prototype MFC using E. coli. 25 It may be due to the fact that different types of mediators act to the different parts of a metabolic pathway. 26 According to Wilkinson, NR most likely interacts with fermentation pathway, not with respiration pathway, which leads to less production of electrons.…”
Section: Resultsmentioning
confidence: 99%